Kinerja Guru Sekolah Dasar di Masa Pandemi Covid-19 - Marhamah, Marhamah (Yayasan Sembilan Pemuda Indonesia, 2021)
The purpose of this study was to determine how the teacher's performance at SD Negeri 27 Banyuasin I. This research was conducted using descriptive qualitative research methods. Sources of data used in this study are primary data and secondary data with data collection techniques, namely interview observation and documentation, the data obtained is then analyzed to become a conclusion of the research process. The findings of the study show that the performance of elementary school teachers at SD Negeri 27 Banyuasin I is still classified as poor because of the five aspects of performance measurement studied, namely the quality of work results, timeliness, ability initiative, and communication, only the aspects of initiative and ability are assessed as having been assessed. pretty good. To improve the performance of elementary school teachers at SD Negeri 27 Banyuasin I, it is hoped that teachers will be more effective and efficient in the learning process so that educational goals can be implemented properly.